Differential intensity‐dependent effects of pulsed electromagnetic fields on RANKL‐induced osteoclast formation, apoptosis, and bone resorbing ability in RAW264.7 cells. Issue 8 (24th July 2017) - Wang, Pan; Liu, Juan; Yang, Yuefan; Zhai, Mingming; Shao, Xi; Yan, Zedong; Zhang, Xuhui; Wu, Yan; Cao, Lu; Sui, Bingdong; Luo, Erping; Jing, Da
Abstract : Pulsed electromagnetic fields (PEMF) have been proven to be effective for promoting bone mass and regulating bone turnover both experimentally and clinically. However, the exact mechanisms for the regulation of PEMF on osteoclastogenesis as well as optical exposure parameters of PEMF on inhibiting osteoclastic activities and functions remain unclear, representing significant limitations for extensive scientific application of PEMF in clinics. In this study, RAW264.7 cells incubated with RANKL were exposed to 15 Hz PEMF (2 h/day) at various intensities (0.5, 1, 2, and 3 mT) for 7 days. We demonstrate that bone resorbing capacity was significantly decreased by 0.5 mT PEMF mainly by inhibiting osteoclast formation and maturation, but enhanced at 3 mT by promoting osteoclast apoptosis. Moreover, gene expression of RANK, NFATc1, TRAP, CTSK, BAX, and BAX/BCL‐2 was significantly decreased by 0.5 mT PEMF, but increased by 3 mT. Our findings reveal a significant intensity window for low‐intensity PEMF in regulating bone resorption with diverse nature for modulating osteoclastogenesis and apoptosis. This study not only enriches our basic knowledge for the regulation of PEMF in osteoclastogenesis, but also may lead to more efficient and scientific clinical application of PEMF in regulating bone turnover and inhibiting osteopenia/osteoporosis. Bioelectromagnetics. 38:602–612, 2017. © 2017 Wiley Periodicals, Inc.